Metabolic pathways to sustainability: review of purple non-sulfur bacteria potential in agri-food waste valorization - Bayon-Vicente, Guillaume; Toubeau, Laura; Gilson, Manon; Gégo, Guillaume; Landgey, Nishitha; Krings, Simone; Leroy, Baptiste (Frontiers in Bioengineering and Biotechnology, 2025)
Agri-food waste (AFW) represents a significant fraction of the material generated by the agri-food industry, which itself accounts for almost one-third of the annual global anthropogenic greenhouse gas (GHG) emissions. Considering the growing global population and the consequent rise in food demand, the management and valorization of this waste are essential to ensure the sustainability of the entire food chain for future generations. Recycling agri-food waste offers a promising strategy to mitigate the sector’s environmental impact, particularly when the waste consists of food-grade materials that enhance its intrinsic value. Retaining such products within the agri-food chain by converting them into feed or food, a process referred to as “waste upcycling,” is therefore of critical importance. Purple non-sulfur bacteria (PNSB) are emerging as promising candidates for AFW upcycling due to their remarkable metabolic versatility, which allows them to metabolize a wide range of organic substrates, including carbohydrates, volatile fatty acids (VFAs), and alcohols, into valuable microbial biomass. This biomass is notably rich in superior quality proteins, vitamins, pigments, and other high-value compounds. The phototrophic metabolism of PNSB is particularly advantageous for organic matter valorization, as the carbon conversion yield approaches unity by utilizing light as an energy source. This review explores the potential of PNSB in upcycling AFW streams derived from various sources, such as fruit and vegetable residues, as well as effluents from the dairy, brewery, and sugar industries. The pre-treatment methods required to optimize substrate availability are also discussed. Furthermore, we examine the metabolic pathways utilized by PNSB under phototrophic conditions to assimilate the most common carbon substrates found in AFW, highlighting critical gaps in our understanding of their metabolism. Additionally, challenges and opportunities in AFW valorization, with a focus on PNSB applications, are identified. This review underscores recent advancements and ongoing challenges, emphasizing the potential role of PNSB in driving sustainable circular bioeconomy applications for AFW.